Laser-Assisted Synthesis of Composite Nanoparticles of Perovskite BaTiO(3) in Aqueous Solutions and Their Optical Properties - Barmina, Ekaterina V. (Materials (Basel), 2020)
Experimental results are presented on laser-assisted synthesis of composite nanoparticles of perovskite BaTiO(3) with gold nanoparticles using the technique of laser ablation in water and aqueous solution of hydrogen peroxide. Nanoparticles of BaTiO(3) are generated by near IR laser radiation with pulse durations of 170 fs, 1 ps, and 200 ns. Nanoparticles of barium titanate BaTiO(3) (BTO) have tetragonal structure for all used pulse durations. Two ways of synthesis are tested. In the first one a gold target is ablated in the colloidal solution of BaTiO(3) nanoparticles. The second way consists of laser exposure of the mixture of colloidal solutions of nanoparticles of BaTiO(3) and Au. Synthesized composite nanoparticles are characterized by optical spectroscopy, Raman spectroscopy, X-Ray diffractometry, and Transmission Electron Microscopy. Composite BaTiO(3)-Au nanoparticles have the absorption band in the visible range of spectrum and demonstrate plasmonic luminescence.